The modulation of information processing by reward expectation and spatial attention - Baines, S; S. Baines (2010)
Reward expectation and spatial attention both exert powerful control over behaviour and modulate neural activity. The experiments in this thesis aimed to chart the dynamics of reward expectation effects across the time course of information processing and examine the relationship between reward and attention. Experiments 3.1 and 3.2 parametrically manipulated reward magnitude in the presence or absence of attention and demonstrated reward could influence reaction time (RT) under conditions of time pressure. Experiments 4.1 and 4.2 independently varied reward and spatial probabilities and illustrated independent and interactive effects of reward and attention at late stages of cognitive processing (the P300 potential), as well as modulation of detection sensitivity (d') by reward under conditions of uncertainty when reward was able to work through feature-based attention. The experiment of Chapter 5 cued reward and attention trial by trial and showed under these conditions, not only could reward influence late stages of information processing, but expectation of reward reduced peak latency of the visual N1 potential. Reward and attention also modulated motor preparation with both independent and interactive effects. The experiment of Chapter 6 examined the dynamics of reward association with task-relevant targets and irrelevant distracters during visual search and demonstrated that task-irrelevant but motivationally-salient distracter items could capture attentional resources away from the target, guided by endogenous reward association alone. The experiments of this thesis demonstrated the ability of reward expectation to modulate both behaviour and multiple stages of information processing, with effects predominantly independent from those of attention. Reward could influence processing from early visual analysis and target detection stages. Interaction between the two systems occurred at late processing stages, whereby reward and attentional information may have been integrated to provide a cohesive representation of the stimulus given the current environmental conditions.